Cutaneous side effects during therapy with Erlotinib: Case report - Jovičić Sanja; Gajanin Vesna; Umičević-Šipka Sanja (Scripta Medica, 2021)
Erlotinib is an antineoplastic drug used in the treatment of non-small cell lung cancer and pancreatic cancer. It is a potent, selective inhibitor of tyrosine kinase, a receptor for epidermal growth factor receptor (EGFR). Cutaneous side effects such as acneiform eruption, xerosis, telangiectasia, hair and nail changes are common. A case of a 70-year-old patient who developed unusual cutaneous side effects after 6 years of treatment with erlotinib was presented.